Climatología del viento y oleaje frente a las costas de Costa Rica, parte 1. - Lizano R., Omar G. (Universidad de Costa Rica, 2009)
The climatologically behavior of the wind and waves is studied around the Costa Rica's coasts using re-analysis data from wave forecasting numeric model. It is found that the wind in the Caribbean coasts of Costa Rica is predominantly from northeast direction all the year. This wind is projected to the north Pacific of Costa Rica through the topographical depression north of Costa Rica and south of Nicaragua generating high wave conditions. The strong trade winds in the boreal winter (north hemisphere) dominate the behavior of the wind in the central and south Pacific coasts of Costa Rica in the first months of the year. This pattern is modified as the Inter-tropical Convergence Zone (ITCZ) migrating to north and then, the westerly wind is intensified over the Pacific coast reaching their maximum expression during September. In respect to waves, it is found that in the Caribbean wave heights are in relationship with the trade wind force over the sea. The relatively short wave period (7 seg) identifies the local wave origin, called "ea", which is chaotic in general and with short wave crests. In the Pacific coast, it is found that the predominant wave direction for all the three distinguishable Costa Rican regions is from the Southwest continued by the south. In the north Pacific, although the predominance of the wind is the zonal component and there is a local wave generation in that direction, it prevails waves with direction from the southwest, indicating that its main wave origin is remote, mainly generated in the south Pacific, like New Zealand , called "well", which are smooth and long wave crests. The monthly climatological analysis of the wave height shows that the Caribbean waves has more energy as the trade wind is intensified (November to April) in the boreal winter. In this time the wave heights in the Pacific coasts is low, changing their pattern when the Caribbean wind weaken (September to October) and the equatorial tropical western is present.